Error comparison between postpaid and prepaid kWh meter readings under load variations - Thania, Visty Chifa; S, Salahuddin; Multazam, Teuku; Yusdartono, Habib Muharry; Fariadi, Dedi (Geuthèë Institute, 2024)
Load variations found in PT PLN Persero customers, such as resistive, inductive, or capacitive loads, can potentially affect the error rate in kWh meter readings. To determine the error rate of kWh meter readings, it is necessary to compare the reading data from each kWh meter with the measurement data from a 6-in-1 multimeter display. This involves comparing the prepaid digital kWh meter, the postpaid semi-digital kWh meter, and the postpaid analog kWh meter, all assembled in series. Based on the test results, the average reading error rate for resistive loads was found to be 0,11% for the prepaid digital kWh meter, 6,91% for the postpaid semi-digital kWh meter, and 0,36% for the postpaid analog kWh meter. For inductive loads, the average reading error rate was 0,36% for the prepaid digital kWh meter, 7,00% for the postpaid semi-digital kWh meter, and 0,27% for the postpaid analog kWh meter. For capacitive loads, the average reading error rate was 0,09% for the prepaid digital kWh meter, 7,52% for the postpaid semi-digital kWh meter, and 0,62% for the postpaid analog kWh meter. This research is important for the electricity supply industry because the accuracy of electrical energy measurement is a key factor in maintaining operational efficiency and improving tariff fairness for customers.